Determination of two different aeration time on food waste composting - Abd Hamid, Khairul Bariyah; Abu Samah, Mohd Armi; Mohd Zainudin, Mohd Huzairi; Yunus, Kamaruzzaman (SpringerLink, 2018)
Increasing volume of organic waste especially food waste due to increased population can affect human and also the environment if it is not managed properly. One of the methods to treat food waste is composting. However, there are many problems regarding composting, for example, time taken to complete the composting process. Thus, the objective for this study is to compare two aeration times used for composting. Methodology for this study started with collecting the food waste, drying and grinding process before starting the composting, and finishing the process in 3 days. Results show that from the two different aeration times, it shows that pH of Compost A (at 34th hour) become neutral faster than Compost B (at 55th hour). There is no significant different for compost temperature between Compost A and Compost B (minimum and maximum). Besides that, total weight reduction for Compost B (45%) is higher compared with Compost A (31%). Even though Compost B is slower to reach pH neutral, it is faster in reduction of total weight. Thus, it can solve the problem especially in increasing volume of food waste.